Association between anti-interferon-alpha autoantibodies and COVID-19 in systemic lupus erythematosus - Gupta, Sarthak (medRxiv, 2020)
OBJECTIVES: Anti-type I interferon (IFN) autoantibodies have been reported in patients with systemic lupus erythematosus (SLE). Recently, an association of these autoantibodies with severe COVID-19 was reported in the general population. We assessed whether having pre-existing anti-IFNα autoantibodies was associated with COVID-19 infection in SLE patients. METHODS: Patients with SLE who developed COVID-19 between April 1(st) to October 1(st), 2020 were studied. Biobanked pre-COVID-19 plasma from these SLE subjects and healthy controls were tested for anti-IFNα IgG autoantibodies by ELISA. The ability of plasma anti-IFNα autoantibodies to block signal transducer and activator of transcription 1 (STAT1) phosphorylation by recombinant human IFNα in vitro was assessed by flow cytometry. RESULTS: Ten SLE subjects with COVID-19 were identified. A 40% of these subjects had stable autoantibodies against IFNα for up to three years preceding COVID-19 diagnosis. A 50% of the subjects with these autoantibodies neutralized IFNα induced STAT1 phosphorylation. None of the other SLE samples blocked IFNα signaling. CONCLUSIONS: We noted an increased prevalence of pre-existing anti-IFNα autoantibodies in SLE patients with COVID-19 compared to the reported prevalence in lupus patients and the general population with severe COVID-19. Autoantibodies against IFNα in SLE patients may be pathogenic and patients with them maybe at-risk of developing COVID-19.